Corn Cost-Return Budget in North Central Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Olson, Brian L.S. (My University, 2007)
This publication provides estimated cost and returns for forward farm planning for corn production in north central Kansas.
MF2161_2007_10
Keywords: MF2161; Crops; Economics; MF